2006
DOI: 10.4209/aaqr.2006.12.0001
|View full text |Cite
|
Sign up to set email alerts
|

Multi-element Analysis and Characterization of Atmospheric Particulate Pollution in Dhaka

Abstract: PIXE (Proton Induced X-Ray Emission) and PIGE (Proton Induced Gamma Ray Emission) have been used to measure the concentration of over 20 elements present in coarse and fine atmospheric particle samples. These samples were collected at a semi-residential site at Dhaka, Bangladesh from July 2002 to June 2003. The multi-elemental capability of PIXE and PIGE enabled the use of these elemental-concentration data to define fingerprints of various coarse and fine particle sources in the atmosphere using factor analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Organic carbon was not measured. The data quality of the available elemental concentration together with mass, BC and delta-C were tested by a reconstructed mass (RCM) analysis comparing the computed RCM values with the gravimetric weight of the filters [7]. The least squares fit to the data were compared with the measured mass in order to check the data quality (Table 2).…”
Section: Multielemental Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Organic carbon was not measured. The data quality of the available elemental concentration together with mass, BC and delta-C were tested by a reconstructed mass (RCM) analysis comparing the computed RCM values with the gravimetric weight of the filters [7]. The least squares fit to the data were compared with the measured mass in order to check the data quality (Table 2).…”
Section: Multielemental Analysismentioning
confidence: 99%
“…These source apportionment studies found that vehicles were normally responsible for about 50% of fine particles (PM 2.5 particles) in Dhaka. Coarse particles (PM 2.5-10 particles) (Particle size 2.5-10 micrometer) mainly originate from mechanical processes [7]. During that period, gasoline and diesel were mainly used as fuel to run motorized vehicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were not determined in this study. Therefore, the reconstructed mass was estimated using the procedures of Malm et al (1994) and Begum et al (2006). An additional variable, unmeasured mass (UMM), was calculated as the difference between the measured mass and the reconstructed mass.…”
Section: Source Apportionment Using Epa Positive Matrix Factorizationmentioning
confidence: 99%
“…These adverse properties demand an assessment of their trends and source profile in the atmosphere to provide an aid to manage regional and local as well as global air pollution strategies [9][10]. Air Pollution related works in Bangladesh are few and most of them are focused to the air quality and characterization of the air pollutant in the capital city Dhaka [11][12][13][14][15][16][17][18][19][20][21]. Salam et al [19] performed the chemical characterization of aerosol in the district Bhola one of the remote island of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%